Biomimetic anti-reflective triboelectric nanogenerator for concurrent harvesting of solar and raindrop energies. (March 2019) - Yoo, Donghyeon; Park, Seung-Chul; Lee, Seoulmin; Sim, Jae-Yoon; Song, Insang; Choi, Dongwhi; Lim, Hyuneui; Kim, Dong Sung
Abstract: As a combination of solar cell and water-based triboelectric nanogenerator (TENG), new concept of a solar-cell-based hybrid energy harvester has been proposed. However, previous studies have not fully considered the degradation of optical characteristics due to water-based TENG and energy loss due to an ineffective electrical connection between solar cell and water-based TENG. The 1% degradation in light transmittance by applying the water-based TENG on its outermost part results in more than 1 mW/cm 2 output power loss in a solar cell, which cannot be recovered by the instantaneous electrical energy output of water-based TENG. Herein, we report a moth's eye mimicking TENG (MM-TENG), which can play a role of complementary energy harvester to a conventional solar cell due to its superior specular transmittance (maximum of 91% for visible light). For the first time, we deeply analyze the optical effect of the MM-TENG on a solar cell by investigating solar-weighted transmittance (SWT). The 0.01% improved SWT in the MM-TENG increases the fill factor and power conversion efficiency of solar cell by 0.5% and 0.17%, respectively, compared with a conventional protective glass plate which is always applied in a solar panel. In addition to such prominent high transmittance, the self-cleaning property of the MM-TENG enables the long-term performance of the solar panel. And particularly, this paper reports a novel electric circuit for effective management in a hybrid energy harvester by intermittently transferring the stabilized electrical energy output of the MM-TENG. This work, which addresses issues for the practical utilization of the water-based TENG as a complementary energy harvester to solar cell, would move the water-based TENG one step closer to its practical utilization by resolving critical concerns. Graphical abstract: fx1 Highlights: A moth-eye mimicking triboelectric nanogenerator with enhanced optical characteristics is reported. The triboelectric nanogenerator enables durable operation of the solar cell under dusty environment. A switching circuit is developed for effective hybrid energy harvesting.